THE INFLUENCE OF INDIVIDUAL FEATURES OF HEART RATE VEGETATIVE REGULATION ON NEUROHUMORAL AND ELECTROPHYSIOLOGICAL EFFECTS OF PROPRANOLOL - Melezhik, Ye.P.; Isaeva, A.S. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 1970)
The study of the vegetative status influence on neurohumoral and electrophysiological effects of  nonselective beta 1,2 – propranolol blocker was the aim of our work.. 13 healthy volunteers at the age of 24±4 years participated in the study. A dose of propranolol made up 0.8 mg/kg per os. The HRV study  was performed on the basis of 5-min ECG recordings which  were made in supine and upright postures before and 90 min after a single propranolol intake. According to the frequency spectral HRV indices that were fixed in supine posture before preparation intake, all theexamined volunteers were divided into two groups with prevalence of sympathetic (LF/HF>1, group A) and parasympathetic (LF/HF<1, group B) activity. According to the HRV recordings in supine posture  the vagotonic effect of the preparation was observed in group A and sympathotonic in group B. In supine position slow-down of the atrial conductivity caused by propranolol was more acute in group B. The neurohumoral and electrophysiological effects of the preparation were less acute when the volunteers were in upright posture. So the dependence of the propranolol effects on the initial neurohumoral regulation status was shown.